INNOVATIVE APPROACH TO FINANCING EXPORTING COMPANIES: Imamova Nasiba Muzafarovna (Ustozlar uchun, 2024)
The national economy development to a qualitatively newlevel, as well as introduction of innovations requires a radical reconsideration ofthe role of exporting companies which hold a particular position have a place inthe economic development. This thesis describes the financing processes ofexporting enterprises.